Monolithic‐Integrated Multiplexed Devices Based on Metasurface‐Driven Guided Waves. Issue 2 (12th January 2021) - Ha, Yingli; Guo, Yinghui; Pu, Mingbo; Li, Xiong; Ma, Xiaoliang; Zhang, Zuojun; Luo, Xiangang
Abstract: The appearance of metasurfaces has solved the difficult problems of bulkiness, the complexity of traditional optics, and arbitrary optical response controlling. However, most free‐space metasurfaces and existing integrated metadevices do not meet the criteria of full on‐chip integration toward low loss and high information transmission capacity. Here, by decorating silicon‐on‐insulator waveguides with metasurfaces, one can realize the arbitrary phase and intensity manipulation of guided waves. Four‐channel multiplexer is demonstrated with inherent advantages of low loss and independent transmission of electromagnetic waves in x and y directions. As proof‐of‐concept demonstrations, monolithic‐integrated multiplexed orbital angular momentum (OAM) and holographic generators are developed at 1550 nm to realize high information transmission capacity, low loss, and low crosstalk. Specifically, when the electromagnetic wave is incident from x, − x, y, and − y directions, four kinds of OAM mode with different topological charge values (−1, +1, +2, and −2), and four different holographic images of the letter "U, " "C, " "A, " and "S" can be obtained with the four‐channel multiplexed OAM generator and holographic display device, respectively. The design methods proposed here are expected to open a new perspective for future versatile utilization of driven guided waves to achieve numerous functionalities. Abstract : Combining the characteristics of independent transmission of guided wave in x and y direction and an ingenious design method, a four‐channel multiplexing orbital angular momentum (OAM) generator is designed, which is used to generate OAM modes with different polarization and different topological charge. In addition, a four‐channel multiplexing generator is introduced to generate four kinds of holograms.